A Review of the Mad Genius: Creativity in Patients with Bipolar Disorder - João Carlos da Costa Teixeira (2022)
Bipolar affective disorder (BD) is an impairing and lifelong subgroup of affective disorders, characterized by depressive and manic or hypomanic episodes. Since the time of Ancient Greece, it has been associated with increased creativity. Association arose after empirically observing an overrepresentation of BD in distinguished artists, such as poets and musicians. Recently, high-quality epidemiological studies started using more methodological approaches, highlighting an association between a standardized measure of creativity and BD, some suggesting that its level may have a role in predicting the diagnosis. The level of creativity seems to be enhanced in unaffected relatives of BD patients, as well as in individuals with genetic vulnerability for the disorder. Though not much is known about the mechanisms that lead to increased creativity, multiple qualities related to BD have been hypothesized, including divergent thinking, impulsivity, ambitiousness, positive affectivity, intuitive cognitive processing, executive function, and openness to experience. There is evidence that subclinical-mild and clinical-moderate levels of BD can have more creative advantages than severe forms of BD, in which cognitive impairment causes compromise of creative thinking. In this article, we provide a summary and critical review of current findings in the field. Since there is still little research regarding the covered topics, we conclude there is a necessity for future investigation, clarification of intergenerational transmission of creativity, mechanisms leading to increased creativity, and potentiation of medication effects.